The accounting estimation of element and structured reliability of corporative telecommunication network on territory of Bryansk region - Lozbinev F.Yu. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2016)
The variant of methods of the accounting estimation of the factor to readiness of multiservice corporative telecommunications of organs of government is presented. The methods of the design estimation of element reliability on base of normative importances structured reliability her pathways and methods of the estimation of the influence on factor of readiness of the pathways of time of the reconstruction of objects of communication are offered. The results of calculation of South, North and West pathways under different variants of equipment and topological scheme, as well as under different manners of the technical maintenance of network are broughted.